Evidence for the stability of the West Antarctic Ice Sheet divide for 1.4 million years - Hein, Andrew; Woodward, John; Marrero, Shasta; Dunning, Stuart; Steig, Eric; Freeman, Stewart; Stuart, Finlay; Winter, Kate; Westoby, Matt; Sugden, David (Nature Communications, 2016)
Past fluctuations of the West Antarctic Ice Sheet (WAIS) are of fundamental interest because of the possibility of WAIS collapse in the future and a consequent rise in global sea level. However, the configuration and stability of the ice sheet during past interglacial periods remains uncertain. Here we present geomorphological evidence and multiple cosmogenic nuclide data from the southern Ellsworth Mountains to suggest that the divide of the WAIS has fluctuated only modestly in location and thickness for at least the last 1.4 million years. Fluctuations during glacial–interglacial cycles appear superimposed on a long-term trajectory of ice-surface lowering relative to the mountains. This implies that as a minimum, a regional ice sheet centred on the Ellsworth-Whitmore uplands may have survived Pleistocene warm periods. If so, it constrains the WAIS contribution to global sea level rise during interglacials to about 3.3 m above present.